2019
DOI: 10.3390/ijms20030745
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Nuclear Ribonucleoproteins Involved in the Functioning of Telomeres in Malignant Cells

Abstract: Heterogeneous nuclear ribonucleoproteins (hnRNPs) are structurally and functionally distinct proteins containing specific domains and motifs that enable the proteins to bind certain nucleotide sequences, particularly those found in human telomeres. In human malignant cells (HMCs), hnRNP-A1—the most studied hnRNP—is an abundant multifunctional protein that interacts with telomeric DNA and affects telomerase function. In addition, it is believed that other hnRNPs in HMCs may also be involved in the maintenance o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 211 publications
(403 reference statements)
0
24
0
Order By: Relevance
“…HNRNPA3 is part of the hnRNP A/B family. The proteins in this family are characterized by two tandem RNA recognition motifs (RRMs) in the N-terminal region 45 , 46 . Systematic analysis of their Drosophila homologs indicates that these hnRNP A/B proteins control overlapping but diverse targets in pre-mRNA processing 47 .…”
Section: Resultsmentioning
confidence: 99%
“…HNRNPA3 is part of the hnRNP A/B family. The proteins in this family are characterized by two tandem RNA recognition motifs (RRMs) in the N-terminal region 45 , 46 . Systematic analysis of their Drosophila homologs indicates that these hnRNP A/B proteins control overlapping but diverse targets in pre-mRNA processing 47 .…”
Section: Resultsmentioning
confidence: 99%
“…7,8 As the most critical alternative splicing regulator, heterogeneous nuclear ribonucleoproteins (hnRNPs) family are responsible for the maturation of pre-mRNAs into functional mRNAs as well as the stabilization of mRNA translocation. 9,10 Through the RNA binding domains (RBDs), hnRNPs accomplish the recognition of specific RNA sequences and control various biological processes of RNA function and metabolism. 11,12 Mechanistically, hnRNPs constitute mRNA-protein 40S core complex via binding to RNA elements including exon and intron splicing regulators, which precisely control the alternative splicing of pre-mRNAs.…”
Section: Introductionmentioning
confidence: 99%
“…As the most critical alternative splicing regulator, heterogeneous nuclear ribonucleoproteins (hnRNPs) family are responsible for the maturation of pre‐mRNAs into functional mRNAs as well as the stabilization of mRNA translocation 9,10 . Through the RNA binding domains (RBDs), hnRNPs accomplish the recognition of specific RNA sequences and control various biological processes of RNA function and metabolism 11,12 .…”
Section: Introductionmentioning
confidence: 99%
“…In our study, the mRBPs HnRNPA1 and HnRNPA2B were found as downregulated SDEG in COPD and this profile was predicted by IPA to inhibit telomere extension by telomerase. Early studies established that hnRNP-A1, hnRNP-A2, and hnRNP-B1 proteins can interact with telomeres and are products of two different genes (HNRNPA1 and HNRNPA2B1) but display similar structures (two RRMs and four RGG motifs in each) (95). The mRBP hnRNP A1 is the best characterized and found to be associated with human telomeres in vivo (96); depletion of hnRNP A/B proteins in human embryonic kidney 293 cell extracts greatly reduced telomerase activity, which was rescued by addition of recombinant hnRNP A1 (96).…”
Section: Discussionmentioning
confidence: 99%